Effect of a pilot washing system on dicofol levels in orange matrix - Ribeiro, M. L.; Amador, JR; Polese, L.; Jardim, EFG; Minelli, E. V.; de Cordis, OCP (Amer Chemical Soc, 2000)
An efficient analytical method is described for the analysis of dicofol residues in pulp and orange peel. Samples are mixed with Celite and transferred to chromatographic columns prepacked with silica gel. Dicofol is eluted with ethyl acetate, and the extracts are analyzed by gas chromatography with electron capture detection. Mean recoveries for dicofol at levels of 0.5, 2.0, 5.0, and 10 mg/kg ranged from 87 to 95% with relative standard deviation values between 2.6 and 9.0%. To investigate the effect of a pilot washing system on dicofol residues in oranges, the analytical procedure was applied to samples submitted to different treatments with commercial formulations under field and laboratory conditions. The orange samples with and without washing were analyzed in duplicate, and the results indicated that washing under the described conditions did not allow a complete removal of dicofol residues from orange peel.
Keywords: dicofol residues; gas chromatography; orange; washing